Toxicological Profile of the Pain-Relieving Antioxidant Compound Thioctic Acid in Its Racemic and Enantiomeric Forms - Elena Lucarini; Elena Trallori; Daniele Tomassoni; Francesco Amenta; Carla Ghelardini; Alessandra Pacini; Lorenzo Di Cesare Mannelli (MDPI AG, 2020)
Thioctic acid is a multipotent antioxidant compound existing as dextrorotatory (+), eutomer and naturally occurring and levorotatory (−). It has been proven to help fight many pathologies and is sold as racemate. In agreement with studies claiming a greater biopotency of the eutomer compared to the levorotatory compound, we recently preclinically and clinically showed that (+) thioctic acid is a pain-reliever as effective as double-dosed racemate. We investigated acute and subchronical toxicity of (+/−) thioctic acid, (−) thioctic acid, (+) thioctic acid and (+) salt thioctic acid on Sprague-Dawley rats. For acute toxicity, compounds were administered intraperitoneally (i.p.) with a single-injection at 125, 240, 360, 480 µmol/kg, then rodents were tested for motorial coordination and minimum lethal dose (LDmin). A subtoxic dose (360 µmol/kg) was administered i.p. for 15 days and we finally evaluated motorial impairment, glycemia, organ toxicity, and apoptosis state. Acutely administered, the highest doses of all thioctic acid compounds negatively affected motorial ability and (−) thioctic acid LDmin resulted higher than the others. Subchronic administrations caused overall body weight loss, motorial impairment, mass loss in some organs. (+/−) and (−) thioctic acid injections enhanced caspase-3 activity in some organs, (−) enantiomer-treated animals displayed more marked organ toxicity signs. Together with our previous study on the biologic role of enantiomers, these data suggest a therapeutic use of (+) enantiomer-based formulations, thus lowering dose and toxicity without affecting the positive effects brought by the drug.